A Comparative Study of Corrosion AA6061 and AlSi10Mg Alloys Produced by Extruded and Additive Manufacturing - Estupiñan López, Francisco Humberto; Gaona Tiburcio, Citlalli; Jáquez Muñoz, Jesús Manuel; Zambrano Robledo, Patricia del Carmen; Cabral Miramontes, José Ángel; Nieves Mendoza, Demetrio; Delgado, Anabel D.; Flores de los Ríos, Juan Pablo; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2021)
The aim of this work was to evaluate the corrosion behavior of the AA6061 and AlSi10Mg alloys produced by extruded and additive manufacturing (selective laser melting, SLM). Alloys were immersed in two electrolytes in H2O and 3.5 wt. % NaCl solutions at room temperature and their corrosion behavior was studied by electrochemical noise technique (EN). Three different methods filtered EN signals, and the statistical analysis was employed to obtain Rn, the localization index (LI), Kurtosis, skew, and the potential spectral density analysis (PSD). The Energy Dispersion Plots (EDP) of wavelets method was employed to determine the type of corrosion and the Hilbert–Huang Transform (HHT), analyzing the Hilbert Spectra. The result indicated that the amplitude of the transients in the time series in potential and current is greater in the AlSi10Mg alloy manufactured by additive manufacturing. The amplitude of the transients decreases in both alloys (AA6061 and AlSi10Mg) as time increases.